Big data and positive social change in the developing world: A white paper for practitioners and researchers - Byarugaba Agaba, G; Akindès, F; Bengtsson, L; Cowls, J; Indira Ganesh, M; Hoffman, N; Hoffman, W; Mann, L; Mans, U; Meissner, F; Meyer, E; Mutuku, L; et al. (Oxford Internet Institute, 2016)
This white paper was produced by a group of activists, researchers and data experts who met at The Rockefeller Foundation’s Bellagio Centre to discuss the question of whether, and how, big data is becoming a resource for positive social change in low- and middle-income countries (LMICs). Our working definition of big data includes, but is not limited to, sources such as social media, mobile phone use, digitally mediated transactions, the online news media, and administrative records. It can be categorised as data that is provided explicitly (e.g. social media feedback); data that is observed (e.g. mobile phone call records); and data that is inferred and derived by algorithms (for example social network structure or inflation rates). We defined four main areas where big data has potential for those interested in promoting positive social change: advocating and facilitating; describing and predicting; facilitating information exchange and promoting accountability and transparency.